Carp Toll-like receptor 8 (Tlr8): An intracellular Tlr that recruits TIRAP as adaptor and activates AP-1 pathway in immune response. Issue 82 (November 2018) - Shan, Shijuan; Liu, Rongrong; Jiang, Lei; Zhu, Yaoyao; Li, Hua; Xing, Weixian; Yang, Guiwen
Abstract: Toll-like receptor 8 (Tlr8) is a member of intracellular TLRs family and play a critical role in the innate immunity. In the present study, we aimed to identify tlr8 from common carp ( Cyprinus carpio L.), and explored its expression profile, localization, adaptor, and signaling pathways. A novel tlr8 cDNA sequence (Cctlr8) was identified from the carp, containing a signal peptide, a LRR-N-terminal (LRR-NT), 14 leucine-rich repeats, a LRR-C-terminal (LRR-CT), a transmembrane region and a TIR domain. Phylogenetic analysis revealed that Cc Tlr8 exhibited closest relationship to that of Ctenopharyngodon idella and Danio. rerio . Subcellular localization analysis indicated that Cc Tlr8 was localized to the endoplasmic reticulum in both HeLa cells and EPC cells. Quantitative Real-Time PCR analysis demonstrated that Cctlr8 was constitutively expressed in all the examined tissues, with the highest expression observed in the spleen. After poly (I:C) injection, the expression of Cctlr8 was significantly up-regulated in all the tested tissues. In addition, the expression of Cctlr8 was up-regulated in both PBLs and HKLs following poly (I:C) stimulation. The results of immuofluorescence and coimmunoprecipitation analysis indicated that Cc Tlr8 might recruit TIRAP as the adaptor. Furthermore, Luciferase reporter assays revealed that Cc Tlr8 could activate AP-1 in 293 T cells. Taken altogether, these findings lay the foundations for future research to investigate the mechanisms underlying fish tlr8 . Highlights: Cc Tlr8 was localized to the endoplasmic reticulum. The expression of Cctlr18 was up-regulated after challenged with poly (I:C). Cc Tlr8 recruited TIRAP as the adaptor. Cc Tlr8 activated AP-1 in 293 T cells.